2011
DOI: 10.1177/1359105311421048
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distance and blood donation intention

Abstract: This study tested Construal Level Theory and examined social desirability and cultural differences as factors affecting blood donation intention across different time frames. Findings showed that individuals indicated stronger intentions for the distant future (one-year and no-time indication frames) than for the near future (one-week and three-month frames). The relationship between social desirability rating of blood donation and intention was positive and significant for the no-time indication frame, but it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 23 publications
1
26
1
1
Order By: Relevance
“…Out of these, 13 studies showed empirical evidence that representing objects or events as high-level construals or as psychologically distant is directly associated with stronger moral judgments and increased moral behavior (Agerström & Björklund, 2009a, 2009bAgerström, Björklund, & Carlsson, 2012Choi, Park, & Oh, 2012;Eyal et al, 2008;Napier & Luguri, 2013;Nordhall & Agerström, 2013;Rixom & Mishra, 2014;Tumasjan, Strobel, & Welpe, 2011;van Houwelingen, van Dijke, & de Cremer, 2015;Yi, Charlton, Porter, Carter, & Bickel, 2011). Two studies showed opposing results such that low-level construals and psychological proximity elicited stronger moral judgment and increased moral behavior (Gong & Medin, 2012;Lammers, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of these, 13 studies showed empirical evidence that representing objects or events as high-level construals or as psychologically distant is directly associated with stronger moral judgments and increased moral behavior (Agerström & Björklund, 2009a, 2009bAgerström, Björklund, & Carlsson, 2012Choi, Park, & Oh, 2012;Eyal et al, 2008;Napier & Luguri, 2013;Nordhall & Agerström, 2013;Rixom & Mishra, 2014;Tumasjan, Strobel, & Welpe, 2011;van Houwelingen, van Dijke, & de Cremer, 2015;Yi, Charlton, Porter, Carter, & Bickel, 2011). Two studies showed opposing results such that low-level construals and psychological proximity elicited stronger moral judgment and increased moral behavior (Gong & Medin, 2012;Lammers, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of cultural differences on the relationship between abstract thinking and moral judgment are examined in only two studies in this review (i.e., Choi et al, 2012;Žeželj & Jokić, 2014a). While the predicted cultural differences did not reach significance in Choi et al's (2012) study, their results indicated that it was unclear for Korean participants whether they perceived one year as psychologically distant or near.…”
Section: Theoretical Standpointsmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, these four distance dimensions appear to have a range of downstream consequences for evaluations, predictions, and behaviors in important domains ranging from negotiation and political behavior to health and cyber security (e.g. Choi, Park, & Oh, 2011;Giacomantonia, De Dreu, & Manetti, 2010;Menegatti & Rubini, 2012;Tam, Glassman, & Vandenwauver, 2010). Given the farreaching implications of the potential link between psychological distance and abstraction, as well as its relevance for researchers interested in studying these central constructs across different areas of psychological science, a quantitative synthesis of existing evidence seems both important and overdue.…”
Section: Downstream Consequences Of Abstractionmentioning
confidence: 99%
“…In the case of blood donation, this result suggests that specific arguments may be more effective than general arguments in persuading people to give blood now (campaigns tend to focus on recruiting donors immediately, rather than at a vague time in the future). In order to test how intention to donate blood varies with temporal distance, Choi et al [12] asked participants to rate their intention to donate blood over four time frames: "in one week", "in three months", "in one year", and no time frame. They found that intentions to donate were stronger with respect to future time frames ("one year" and no time frame) than with respect to more immediate time frames.…”
Section: Introductionmentioning
confidence: 99%